Work-related Hazards Among Pathologists and Residents of Pathology: Results of a Cross-sectional Study in Iran - Maryam Kadivar; Elaheh Kabir-Mokamelkhah; Zohreh Habibi-Shams (Iranian Journal of Pathology, 2021)
Background & Objective: Pathologists as medical professionals involved in the diagnosis and planning of therapies in many diseases are exposed to occupational hazards in workplaces. Hence, we aimed to determine the occupational health problems among Iranian pathologists in this cross-sectional study.Methods: This cross-sectional study was conducted among the Iranian pathologists. The data required for this study was collected through a self-reported questionnaire containing 48 questions about major occupational health problems, including musculoskeletal problems, visual disorders, workplace characteristics, health behavior, and other medical conditions.Results: Among the study participants (N=350), 87.4% presented with musculoskeletal disorders in the past year, with the neck as the most common location of pain (71%). Musculoskeletal pain was significantly higher in those working with the computer for more than 5 hours per day (P=0.007). Furthermore, 273 (78%) participants reported visual refractive errors, and myopia was the most common error (53%). Acute injuries were reported in 263 (75%) participants, and the cutting injury had the highest frequency (56.6%). Depression was reported in 54 (15.4%) of the participants, followed by burnout (10.3%) and hypertension (4%). Intolerance reactions to formalin were reported by 222 (63.6%) and were significantly more frequent among the residents (p <0.001). The residents were more prone to musculoskeletal pain (P=0.002) and injury (P=0.026). Conclusion: We observed a noticeable prevalence of health risks, including musculoskeletal problems, visual disturbances, injuries, and ergonomic problems among the Iranian pathologists. Solving these problems demands thorough prevention and personal protection, as well as educational programs with more attention toward optimization of ergonomics in the workplace and awareness about chemical and biological hazards.